Donor Darah Dalam Kegiatan Hari Bakti Dokter Indonesia di Halaman Bolak Kota Padangsidimpuan - Nasution, Dina Rahmi Solihad (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2024)
Blood is an important part of the body whose main function is to transport nutrients and materials throughout the body to achieve a homeostasis (balanced) state. Blood grouped into four groups, namely A, B, AB, and O. The purpose of this community service is as a medium to increase insight into the benefits of blood transfusions both for oneself and for recipients in need. This activity will be held on June 9, 2024 at Alaman Bolak Padangsidimpuan. The activities carried out began with health checks, blood donations and ended with the distribution of shopping vouchers. This community service uses a participatory model method. The results of this activity were obtained by 30 voluntary blood donation participants consisting of adolescents to adults and then 15 bags of blood products were obtained. This service is expected to be a medium for promoting independent health in the community so that public interest in donating blood increases